MOTIVASI BELAJAR DITINJAU DARI DUKUNGAN SOSIAL ORANGTUA PADA SISWA SMA - Martina Winarni, Sri Anjariah dan Muslimah Z.Romas (Jurnal Psikologi, 2006)
Thorough two questionnaires, 154 students were asked either their social parental supports or motivational on academic learning. They were on grade 11, and their school was located in Gunung Kidul Regency, east side of Yogyakarta Province. It was expected that there was a positive correlation between the social parental support and children's motivation on academic learning. Data on the social parental support were collected through four factors i.e. information supply, emotional support, evaluation, and physical supply (money, transportation, books, etc.). Further on, data on students motivational were collected through six factors i.e. interest, need, aspiration, attitude, value, and incentive. Research result was that there was not any correlation between the social parental support and students motivational. One explanation was that the motivational factor should be focused more on one subject such as math, instead of whole subjects.